Assessment of prescribed fire and cutting as means of controlling the invasion of sub‐alpine grasslands by Echinospartum horridum. Issue 2 (11th January 2018) - Nuche, Paloma; Komac, Benjamin; Gartzia, Maite; Villellas, Jesús; Reiné, Ramón; Alados, Concepción L.
Abstract: Aims: Sub‐alpine grassland ecosystems have some of the highest biodiversity in Europe and constitute high‐value natural resources. These grasslands are under threat because of the abandonment of traditional agro‐pastoral activities and subsequent invasion by woody species. In the Central Pyrenees (Spain) several management techniques have been used to stop expansion of the highly encroaching shrub Echinospartum horridum . However, the ways in which these techniques affect recovery of sub‐alpine grasslands are poorly understood. The final goal of this study is to gain information about the effects of E. horridum management practices and provide recommendations for the local stakeholders. Methods: This study evaluated the efficacy of controlled fires and mechanical removal of above‐ground vegetation in controlling expansion of E. horridum into sub‐alpine grasslands in the Central Pyrenees. E. horridum demography (germination and survival), soil seed bank and soil properties were recorded in two E. horridum stands where vegetation was previously removed by (1) fire (burning treatment) or (2) mechanical removal (cutting treatment) and (3) an undisturbed E. horridum stand (control). Results: The burning treatment increased germination and survival of E. horridum seedlings more than the cutting treatment, relative to the control. Therefore, cutting appeared to be a better option for controlling E. horridum . Soil seed density was higher in the management treatments than in the control, but it did not harbour sub‐alpine grasslands species. E. horridum removal favoured recharge of the soil with seeds that arrived by dispersal. The soil seed bank in the burning treatment had higher seed abundance and seed diversity than in the cutting treatment; however, fire promoted a loss of soil nutrients. Conclusions: The soil seed bank composition (low abundance and diversity of native species) coupled with rapid regeneration rate of E. horridum would prevent recovery of the sub‐alpine grassland based on the soil seed bank alone. Traditional shepherding has been reported to favour seed dispersal, and here we recommend E. horridum removal with cutting treatment as an additional practice for integrated management and recovery of the sub‐alpine grasslands. Abstract : Burning and clearing were investigated as techniques for recovering the original subalpine grassland vegetation after shrub encroachment. Both treatments removed the shrubs and recharged the soil seed bank, but also favored shrub regeneration, and did not harbor seeds of grassland species. Therefore, these treatments need to be combined with additional strategies that slow‐down shrub regeneration and favor subalpine seed dispersal.